Ulcerative Colitis Activity Presenting as Fever of Unknown Origin, in a Patient with Longstanding Disease under Continuous Treatment with Mesalazine - Panagiota Voukelatou; Elissavet Sfendouraki; Theodoros Karianos; Sofia Saranti; Dimitrios Tsitsimelis; Ioannis Vrettos; Andreas Kalliakmanis (Case Reports in Medicine)
Background. The presence of ulcerative colitis (UC) with no bowel symptoms, as fever of unknown origin (FUO), is uncommon. Objective. To describe the case of an 80-year-old woman who presented with fever, with a history of UC under treatment with mesalazine. Case Presentation. She was admitted due to fever lasting for 12 days with no associated symptoms. Seven years earlier, she was diagnosed with UC. After an extended workup for FUO that failed to reach the diagnosis, she underwent a gallium-67 scintigraphy. This revealed a persistent diffuse concentration of gallium-67 in the ascending colon at 24-hour imaging that remained stable at 48- and 72-hour imaging without any topographic change after the use of laxatives. Considering the results and in the absence of another diagnosis, the patient was treated with 30 mg prednisone daily and mesalazine, as treatment of active UC. Subsequently, the patient’s condition improved markedly and the fever retreated. One month later, she was reevaluated with a gallium-67 scintigraphy with total absence of gallium-67 concentration in the ascending colon. Conclusion. UC activity must be included in the differential diagnosis of FUO in patients with longstanding disease, since fever may present alone, with no other manifestations.